TiN-based electrochemical NO2 gas sensor and preparation method thereof
By using TiN materials with high specific surface area and abundant nitrogen vacancy sites, the electrochemical NO2 gas sensor was constructed, which solved the problems of poor selectivity and insufficient stability of NO2 in the prior art, and realized an efficient and low-cost gas sensor design, especially High stability in low temperature and humid environments.
Patent Information
- Application Number
- CN202411264235.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-10
AI Technical Summary
Existing gas sensors have poor selectivity for nitrogen dioxide (NO2) and insufficient long-term stability, especially the high cost and low stability problems based on Pt/C materials, and the nucleation of traditional transition metal nitrides (TMNs) such as TiN and There are significant activation energy disorders during the crystallization process, resulting in low selectivity and poor stability.
TiN material with high specific surface area and nitrogen vacancy site was used to synthesize TiN through the preparation of MIL-125 (Ti) and ammonialysis reaction, and the catalyst ink was prepared by sonicating Nafion solution and isopropanol, and drip-cast on the surface of carbon paper. And a film electrode assembly is formed by hot pressing to construct an electrochemical NO2 gas sensor.
It significantly improves the selectivity and long-term stability of gas sensors, reduces costs, solves the stability problems of traditional materials in low temperature and humid environments, and improves the gas diffusion, adsorption and catalytic reaction characteristics.
Smart Images

Figure CN119125280A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of gas sensor technology, in particular to a TiN-based electrochemical NO 2 Gas sensor and method for preparing the same. Background Art
[0002] With the rapid development of industrialization and urbanization, air pollution has become increasingly serious, especially nitrogen dioxide (NO 2 ) emissions not only cause damage to the respiratory system, but are also closely related to the development of chronic diseases such as asthma. It is listed as one of the six major air pollutants by the US Clean Air Act and the World Health Organization. Currently, about 99% of the world's population is exposed to air that does not meet WHO standards. Therefore, monitoring NO in the air is very important. 2 Pollution is critical to protecting public health. The U.S. Environmental Protection Agency defines NO 2 The annual average safety concentration is set at 53ppb. More than 117 countries around the world are actively involved in using various gas sensors for air detection. The performance of gas sensors depends on gas sensitive materials. Such sensitive materials increase sensitivity by increasing specific surface area and reaction sites. However, current sensitive materials such as metal oxide semiconductors (MOS) such as SnO 2 The selectivity of Pt / C materials is poor and the high-performance electrochemical sensors based on Pt / C materials are expensive and lack long-term stability.
[0003] Recent studies have explored new materials for high-performance gas sensors, such as: 1) Quantum dots (QDs) dispersed in gels can increase the specific surface area and gas active sites, but the stability is poor, such as PdCdSe QDs, the effect decays by 10% after 75h; 2) Single atom catalysts (SACs) improve electron transport by exposing the surface and dispersing active sites at the atomic level, but face the challenges of low synthesis efficiency and poor stability; 3) Transition metal nitrides (TMNs), such as titanium nitride (TiN), have attracted much attention due to their high electronic conductivity and excellent chemical stability. However, due to the significant activation energy barriers during nucleation and crystallization, it is challenging to develop TMNs with high specific surface area and catalytic activity, and the resulting gas sensors are not highly selective and have poor long-term stability. Summary of the invention
[0004] 1. Technical issues to be solved
[0005] In view of the shortcomings of the prior art, the present invention provides an electrochemical NO 2 The gas sensor and the preparation method thereof improve the selectivity and long-term stability of the gas sensor through a specific TiN material, and solve the problems raised in the above background technology.
[0006] (II) Technical solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] According to a first aspect of the present invention, there is provided a TiN-based electrochemical NO 2 A gas sensor, comprising a membrane electrode assembly, a working electrode sheet, a counter electrode sheet and a cathode sealed gas chamber;
[0009] Wherein, the membrane electrode assembly contains TiN.
[0010] Preferably, the metal sites of the TiN are surrounded by abundant nitrogen vacancies, and the specific surface area of the TiN is 34 to 222 m 2 / g.
[0011] According to a second aspect of the present invention, there is provided a TiN-based electrochemical NO 2 The method for preparing a gas sensor comprises the following steps:
[0012] (1) Preparation of MIL-125(Ti)
[0013] H 2 BDC and TTIP are added to a mixed solution containing N,N-dimethylformamide and methanol, heated at 150-160° C. for reaction for 16-24 hours, filtered, washed alternately with N,N-dimethylformamide and methanol for 3-5 times, and dried to obtain the MIL-125(Ti);
[0014] (2) Preparation of TiN
[0015] The MIL-125 (Ti) powder is placed in a ceramic boat, and then the ceramic boat is sealed in a tube furnace, high-purity ammonia is introduced to perform an ammonolysis reaction, and then cooled to room temperature to obtain the TiN;
[0016] (3) Electrochemical NO 2 Preparation of gas sensors
[0017] The TiN is dissolved in a mixed solution containing a Nafion solution and isopropanol and subjected to ultrasonic treatment to obtain a catalyst ink; the catalyst ink is then drop-casted onto a carbon paper surface at 80 to 100° C., a Nafion N-115 membrane is sandwiched between two carbon papers, and two polytetrafluoroethylene membranes are attached to the surface of the carbon paper, and hot-pressed at 80 to 100° C. and 1 to 3 MPa for 60 to 180 seconds, and the polytetrafluoroethylene membrane is peeled off to obtain the membrane electrode assembly;
[0018] The membrane electrode assembly is bonded to the working electrode sheet and the counter electrode sheet to form a small fuel cell, and the cathode of the small fuel cell is sealed with a cathode sealing gas chamber to obtain the electrochemical NO 2 Gas sensor.
[0019] Preferably, in step (1), the H 2 The molar ratio of BDC to TTIP is 1.5 to 3:1;
[0020] The volume ratio of N,N-dimethylformamide to methanol in the mixed solution containing N,N-dimethylformamide and methanol is 0.5-1.5:1.
[0021] Preferably, in step (2), the heating rate of the ammonolysis is 3 to 8°C / min, the temperature of the ammonolysis is 500 to 900°C, and the time of the ammonolysis is 3 to 5h.
[0022] Preferably, in step (2), the flow rate of the ammonia gas is 50 to 150 cm 3 / min.
[0023] Preferably, in step (3), the mass of the TiN is 0.5 to 1.5 mg.
[0024] Preferably, in step (3), the volume ratio of the Nafion solution to the isopropanol in the mixed solution containing the Nafion solution and isopropanol is 1:11.5;
[0025] The concentration of the Nafion solution is 5-20 wt %.
[0026] Preferably, after obtaining the membrane electrode assembly, the process further includes cutting the membrane electrode assembly into sizes that match the working electrode sheet and the counter electrode sheet, and the membrane electrode assembly is bonded to the stainless steel electrode by hot melt adhesive.
[0027] (III) Beneficial effects
[0028] The present invention provides a TiN-based electrochemical NO 2 Gas sensor and its preparation method. Have the following beneficial effects:
[0029] (1) This scheme provides a TiN-based electrochemical NO 2 The gas sensor uses TiN material with high specific surface area and NVs sites, which significantly enhances the properties of gas diffusion, adsorption and catalytic reaction. Compared with the traditional gas sensor that loads Pt on the sensitive material to enhance the gas response, it not only significantly reduces the cost of the gas sensor, but also solves the problem of poor long-term stability of Pt nanoparticles due to shedding and aggregation during long-term operation.
[0030] (2) This scheme provides a TiN-based electrochemical NO 2 The gas sensor, because it uses TiN material with high specific surface area and NVs sites, has high stability in low temperature and humid environment, and is less affected by low temperature and humid environment.
[0031] (3) This scheme provides a TiN-based electrochemical NO 2 Preparation method of gas sensor, by ammoniolysis of MOF-MIL-125 (Ti), the synthesized TiN material has an ultra-high specific surface area, up to 221.9m 2 / g and has abundant NVs sites, which solves the problem of significant activation energy barriers in the nucleation and crystallization processes of traditional TMNs. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the preparation process of TiN of the present invention;
[0033] Figure 2 X-ray diffraction patterns of MIL-125 (Ti) powder and TiN prepared in Examples 1 to 5, wherein a) is the XRD pattern of MIL-125 (Ti) powder; b) is the XRD pattern of TiN-600; c) is the XRD pattern of TiN-500, TiN-700, TiN-800, and TiN-900;
[0034] Figure 3 The TiN prepared in Examples 1 to 5 and the commercially available TiN were subjected to N 2 Adsorption-desorption isotherms;
[0035] Figure 4 Transmission electron micrographs of the MIL-125 (Ti) powder and TiN prepared in Example 1, wherein a) is the HRTEM image of TiN-600; b) is the HRTEM image of MIL-125 (Ti); c) is the filtered image of the boxed area in a);
[0036] Figure 5 The electrochemical NO prepared in Example 1, Comparative Example 1 and Comparative Example 2 2 Selective view of gas sensors for different analytical gases;
[0037] Figure 6 The electrochemical NO prepared in Examples 1 to 4 2 Gas sensor for 50ppm NO 2 Response transient curve;
[0038] Figure 7 The electrochemical NO prepared in Example 12 The gas sensor is sensitive to 50ppm NO 2 Response recovery transient curve;
[0039] Figure 8 The electrochemical NO prepared in Example 1 2 Gas sensor for 50ppm NO 2 Response changes within 130 days. DETAILED DESCRIPTION
[0040] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] The preparation process of TiN in this embodiment is as follows Figure 1 As shown:
[0043] Preparation of MIL-125(Ti): 1000 mg of H 2 BDC and 864 mg of TTIP were added to a mixed solution of 25 mL of DMF and 25 mL of methanol, stirred thoroughly at room temperature, and then transferred to a 100 mL Teflon-lined autoclave, heated at 150 ° C for 16 h, filtered to collect the residue, washed alternately with DMF and methanol three times, and dried to obtain a white solid MIL-125 (Ti) powder;
[0044] Preparation of TiN: 100 mg of MIL-125 (Ti) powder was placed in a ceramic boat in a tube furnace. 3 Ammonia gas was continuously introduced at a flow rate of 1 / min, and then the temperature was raised to 600°C at a rate of 5°C / min and maintained for 3 hours for ammonolysis. After the end, ammonia gas was continuously introduced until the tubular furnace was cooled to room temperature to obtain TiN, which was recorded as TiN-600.
[0045] Electrochemical NO 2 Preparation of gas sensor: 5 mg of TiN-600 powder, 40 μL of 5 wt% Nafion solution and 460 μL of isopropanol were ultrasonically treated to obtain catalyst ink, and then the catalyst ink was drop-cast onto a carbon paper surface at 90°C, and then a Nafion N-115 membrane was sandwiched between two carbon papers, and two polytetrafluoroethylene membranes were attached to the surface of the carbon paper, and hot-pressed at 90°C and 1 MPa for 120 s, and the polytetrafluoroethylene membrane was peeled off to obtain the membrane electrode assembly;
[0046] The obtained membrane electrode assembly is cut into a size suitable for the working electrode sheet and the counter electrode sheet, and is bonded to the stainless steel electrode by hot melt adhesive to form a small fuel cell. The cathode of the small fuel cell is sealed with a cathode sealing gas chamber to obtain an electrochemical NO 2 The gas sensor is denoted as TiN-600 sensor.
[0047] Example 2
[0048] The preparation method of this embodiment is the same as that of embodiment 1, except that the temperature of the ammonolysis in step (2) is 500°C, the obtained TiN is denoted as TiN-500, and the obtained electrochemical NO 2 The gas sensor is denoted as TiN-500 sensor.
[0049] Example 3
[0050] The preparation method of this embodiment is the same as that of embodiment 1, except that the temperature of the ammonolysis in step (2) is 700°C, the obtained TiN is denoted as TiN-700, and the obtained electrochemical NO 2 The gas sensor is denoted as TiN-700 sensor.
[0051] Example 4
[0052] The preparation method of this embodiment is the same as that of embodiment 1, except that the temperature of the ammonolysis in step (2) is 800°C, the obtained TiN is denoted as TiN-800, and the obtained electrochemical NO 2 The gas sensor is denoted as TiN-800 sensor.
[0053] Example 5
[0054] The preparation method of this embodiment is the same as that of embodiment 1, except that the temperature of the ammonolysis in step (2) is 900°C, the obtained TiN is denoted as TiN-900, and the obtained electrochemical NO 2 The gas sensor is denoted as TiN-900 sensor.
[0055] Comparative Example 1
[0056] The preparation method of this embodiment is the same as that of embodiment 1, except that the sensitive material used in step (3) is commercially available TiN-CM material.
[0057] Comparative Example 2
[0058] The preparation method of this embodiment is the same as that of embodiment 1, except that the sensitive material used in step (3) is the traditional Pt / C material.
[0059] Performance measurement of TiN prepared in Examples 1 to 5:
[0060] X-ray diffraction was performed on the MIL-125 (Ti) powder and TiN prepared in Example 1 of the present invention and the TiN prepared in Examples 2 to 5, respectively. Figure 2 As shown, the present invention successfully prepared MIL-125 (Ti) powder and TiN, and used MOF as a sacrificial template to synthesize TiN by precisely controlling the temperature of the ammonolysis process, while retaining the high specific surface area structure of MOF, forming abundant NVs sites around the metal sites.
[0061] The TiN prepared in Examples 1 to 5 of the present invention and the TiNTiN-CM purchased directly were respectively subjected to N 2 Adsorption-desorption tests, such as Figure 3 As shown, according to Figure 3 It can be seen that TiN derived from MOF has a higher specific surface area, and the specific surface area of TiN-600 reaches 221.9 m 2 / g, which is 90 times that of TiN-CM.
[0062] according to Figure 4 From the transmission electron micrographs, it can be seen that Figure a) shows a series of lattice fringes associated with the (331) and (400) crystal planes of TiN-600, showing randomly oriented grains. The boxed area of Figure a) shows the scanning electron microscope image of TiN-600, which presents a uniform square morphology, which is consistent with the morphology of the precursor MIL-125(Ti) shown in Figure b), indicating that MIL-125(Ti) still maintains its morphology after low-temperature ammonolysis and obtains abundant surface active sites. According to Figure c), the discontinuity of the lattice fringes and the blurring or missing of some lattice sites indicate the presence of vacancy defects, which can serve as active centers, thereby increasing catalytic activity.
[0063] Performance comparison of the gas sensors prepared in Examples 1 to 5 and Comparative Examples 1 to 2:
[0064] The selectivity of the gas sensors of Example 1 and Comparative Examples 1-2 to different analytical gases is analyzed. Figure 5 As shown in the figure, the TiN-600 sensor is sensitive to NO 2 The response of the TiN-600 sensor to NO is significantly higher than that of the TiN-CM sensor and the Pt / C material sensor. The response to various interfering gases (including 300ppm NO, acetone, methanol, trimethylamine, ammonia, hydrogen and ethanol) is low and negligible, indicating that the TiN-600 sensor has a good sensitivity to NO. 2 Highly selective.
[0065] By monitoring the NO in Examples 1 to 4 2 Gas sensor for NO 2 Response, such as Figure 6 As shown, the sensor using TiN-600 exhibits the highest response. Figure 7 As shown, the TiN-600 sensor is sensitive to 50ppm NO 2 The response and recovery times are 7.4s and 5.2s respectively, which is a quick response.
[0066] according to Figure 8 As shown, the sensing response of the TiN-600 sensor was tested for up to 130 days, and it was found that the response at 130 days only decreased by 3.3% compared with the first day, showing excellent long-term stability.
[0067] According to the above test results, the present invention optimizes the preparation process of TiN material to obtain electrochemical NO 2 Gas sensor with excellent NO 2 Gas selectivity and stability.
[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A TiN-based electrochemical NO2 gas sensor, characterized in that: It includes a membrane electrode assembly, a working electrode sheet, a counter electrode sheet and a cathode sealing gas chamber; Wherein, the membrane electrode assembly contains TiN.
2. The TiN-based electrochemical NO2 gas sensor according to claim 1, characterized in that: The metal sites of the TiN are surrounded by abundant nitrogen vacancies, and the specific surface area of the TiN is 34 to 222 m 2 / g.
3. A method for preparing a TiN-based electrochemical NO2 gas sensor as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of MIL-125(Ti) Adding H2BDC and TTIP to a mixed solution containing N,N-dimethylformamide and methanol, heating the mixture at 150-160° C. for reaction for 16-24 hours, filtering, washing with N,N-dimethylformamide and methanol alternately for 3-5 times, and drying to obtain the MIL-125(Ti); (2) Preparation of TiN The MIL-125 (Ti) powder is placed in a ceramic boat, and then the ceramic boat is sealed in a tube furnace, high-purity ammonia is introduced to perform an ammonolysis reaction, and then cooled to room temperature to obtain the TiN; (3) Preparation of electrochemical NO2 gas sensor The TiN is dissolved in a mixed solution containing a Nafion solution and isopropanol and subjected to ultrasonic treatment to obtain a catalyst ink; the catalyst ink is then drop-casted onto a carbon paper surface at 80 to 100° C., a Nafion N-115 membrane is sandwiched between two carbon papers, and two polytetrafluoroethylene membranes are attached to the surface of the carbon paper, and hot-pressed at 80 to 100° C. and 1 to 3 MPa for 60 to 180 seconds, and the polytetrafluoroethylene membrane is peeled off to obtain the membrane electrode assembly; The membrane electrode assembly is bonded to the working electrode sheet and the counter electrode sheet to form a small fuel cell, and the cathode of the small fuel cell is sealed with a cathode sealing gas chamber to obtain the electrochemical NO2 gas sensor.
4. The method for preparing a TiN-based electrochemical NO2 gas sensor according to claim 3, characterized in that: In step (1), the molar ratio of H2BDC to TTIP is 1.5 to 3:1; The volume ratio of N,N-dimethylformamide to methanol in the mixed solution containing N,N-dimethylformamide and methanol is 0.5-1.5:
1.
5. The method for preparing a TiN-based electrochemical NO2 gas sensor according to claim 3, characterized in that: In step (2), the heating rate of the ammonolysis is 3 to 8°C / min, the temperature of the ammonolysis is 500 to 900°C, and the time of the ammonolysis is 3 to 5h.
6. The method for preparing a TiN-based electrochemical NO2 gas sensor according to claim 3, characterized in that: In step (2), the flow rate of the ammonia gas is 50 to 150 cm 3 / min.
7. The method for preparing a TiN-based electrochemical NO2 gas sensor according to claim 3, characterized in that: In step (3), the mass of the TiN is 0.5 to 1.5 mg.
8. The method for preparing a TiN-based electrochemical NO2 gas sensor according to claim 3, characterized in that: In step (3), the volume ratio of the Nafion solution to the isopropanol in the mixed solution containing the Nafion solution and isopropanol is 0.5-1.5:11.5; The concentration of the Nafion solution is 5-20 wt %.
9. The method for preparing a TiN-based electrochemical NO2 gas sensor according to claim 3, characterized in that: After obtaining the membrane electrode assembly, the process also includes cutting the membrane electrode assembly into sizes that match the working electrode sheet and the counter electrode sheet, and bonding the membrane electrode assembly to the stainless steel electrode by hot melt adhesive.
Citation Information
Patent Citations
Au-coated NH2-MIL-125 (Cu / Ti) photocatalyst as well as preparation method and application thereof
CN114471727A
Hollow tubular Pt / TiN gas-sensitive electrode material as well as preparation method and application thereof
CN118112071A
Nitrogen oxide gas sensor
JP1999072476A
Titanium heterometallic metal-organic solids, method for obtaining them and their uses
US20210261577A1
KR20230017053A
